Bahasa Inggris - Harida, Eka Sustri; Siregar, Sri Rahmadhani; Diana, Pati; Rahmadani, Addini Hayatunnuha (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2025)
Reading is finding information in what we read. Sometimes readers had difficulties with it. This study aimed to identify the students’ difficulties in reading and to identify the solution of AI that they used. The sources are the English students at UIN Syahada Padangsidimpuan. It is a mixed-method study by using closed interviews, questionnaires, and giving reading tests, and to get the data. Data had been analyzed by reading, grouping, coding, and giving interpretation, then by descriptive statistics. The findings showed that the students had difficulties in finding detailed information, finding the contrasting ideas, and identifying major sentence. Then, 65% of the students used AI tool; the most commonly used are Chat-GPT and Google Translate. They knew a lot about AI; however, they were not interested in using it because it is difficult to understand. It is implied that the students need to learn more to be able to understand the contents while reading English texts. They also need to be able to use many applications in their English reading, and be careful not to be suspended in using AI. The English lecturers need to teach the students to practice reading ability and using AI carefully.